Dari tradisi ke pendidikan: Peran ziarah makam dalam membentuk karakter siswa MTS Kanjeng Sepuh - Nisa', Ismi Khoirun (Maliki Interdisciplinary Journal, 2025)
The tradition of visiting graves is one form of preserving spiritual and cultural values in Islamic education. This article discusses the routine activity of visiting the grave of Mbah Kanjeng Sepuh, which is held every 25th by all students, teachers, and staff of MTs Kanjeng Sepuh Sidayu Gresik. This tradition is not only a form of respect for the founders of the madrasa but also an effective means of character education to instill religious, social, and communal values. The method used in this writing is qualitative descriptive with an observational and documentation approach to activities. The results of the discussion show that this monthly pilgrimage has a positive impact on students' spiritual attitudes and strengthens emotional bonds among madrasa members. Therefore, this tradition needs to be preserved and developed as an integral part of the educational process in the madrasa environment.